Горн кінця XV – початку XVI ст. із старої частини м. Чернівців - Калініченко, Віталій; Ільків, Микола; Пивоваров, Сергій (Київ, Інститут археології НАН України, 2018)
In 2014 the remains of a one-chamber pottery kiln were investigated on the high left bank of Ruda River in the old part of Chernivtsi. The southern part of the construction was destroyed by a landslide. Fragments of the several dozen vessels and the coin of Stefan cel Mare 1480-1504 were found in the kiln. Shapes of the nine pots and jugs were restored. The structure of the pottery kiln, the morphology of the pottery and the numismatic find allow to date the complex with the end of the 15th – the beginning of the 16th century.
Pottery kiln of the end of the 15th – the beginning of the 16th century from the old part of Chernivtsi
Keywords: гончарний горн; Чернівці; глек; горщик; монетна знахідка